PENGARUH KOMUNIKASI ELECTRONICWORD OF MOUTH TERHADAP KEPERCAYAAN (TRUST) DAN NIAT BELI (PURCHASE INTENTION) SERTA DAMPAKNYA PADA KEPUTUSAN PEMBELIAN (Survey Pada Konsumen Online Shopping Zafertech.Com) - Syafaruddin Z (University of Merdeka Malang, 2017)
The growth of information technology have brought changes to the development of the business word , and it is widely used by businessmen to compete in their marketing activities .thereford, the marketing activities growth broadly and complex .contemporaly, consumers are more easily to exchange the information with other consumers in choosing products that they would buy. The communication of Word of Mouth ( WOM ) becomes essential in marketing, because it can be influence consumer purchasing decision. Acordingly the communication of WOM have more trust compare to others marketing communication forms. The aim of this research is to find out and explain the influence of EWOM communication form toward Trust, Purchase Intention and purchase decisions. The type of this research is explanatory research. Object the research is consumers at Zafertech.com online shopping with 97 samples. The analysis method is using GSCA (generalized structured component ) analysis. Purposive Sampling is used in this research. The results show 1 ) the electric communication of WOM have a significant influence toward Trust, 2 ) the electric communication of WOM have a significant influence toward Purchase Intention, 3 ) the electric communication of WOM have a significant influence toward purchasing decision (4) trust have a significant influence toward Purchase Intention, (5) trust have a significant influence toward purchasing decision, and (6) Purchase Intention have a significant influence toward purchasing decision.